A new species of Xenylla Tullberg, 1869 (Collembola: Hypogastruridae) from Central Amazon, Brazil - Neves, Ana C. R.; Mendonça, Maria C. (Zootaxa, 2017)
A new species of the cosmopolitan genus Xenylla Tullberg, 1869 is herein described and illustrated. The new species, Xenylla hodori sp. nov., from the Amazon Forest of Northern Brazil, resembles X. capixaba Fernandes & Mendonça, 2010 and X. welchi Folsom, 1916 due, the number of eyes, chaetotaxy head and shape of furca. X. hodori sp. nov. is the second species recorded for the Brazilian Amazon Region.